Effect of Rote Tortoise Habitat on Morphology and Anatomical Systems of the Body and Government Efforts to Overcome Extinction - Resti Nopriyanti; Jennie Agatherania Listira; Dominica Feni Valentina; Wahyu Irawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The Rote turtle with the scientific name Chelodina mccordi is an endemic animal from Rote Island, East Nusa Tenggara. The Rote turtle is unique in its long neck and snake-like head. Rote turtles are rarely found in their natural habitat because many are hunted to be traded by collectors of endemic reptiles. The purpose of this study was to determine the effect of the habitat and behavior of the rote tortoise on its morphology and body mechanisms. The method used to compile this paper is to use literature reviews and literature studies from various sources to discuss 5 topics of study, namely: Rote Turtle Habitat, Rote Turtle Morphology, Blood Circulation System, Rote Turtle Respiratory System, Osmoregulation and Excretion of the Rote Turtle, and Uniqueness and Management of the Rote Turtle. Based on the results obtained, the habitat of the Rote turtle greatly influences the morphology and mechanisms of blood, respiration, osmoregulation, and excretion of the Rote turtle. The habitat for tortoise rote is the appropriate physical environment. Low rainfall of around 800-1200 mm/year and swamp grass with a height of about 2-3 meters. Potential predators for food and hunting have caused the Rote tortoise to become rare and rarely found in its natural habitat. The NTT government has designated three natural habitat lakes are natural habitats and the Governor of NTT Decree Number: 204/KEP/HK/2019 made the rote turtle habitat for the rote turtle Essential Ecosystem Area.